Family Welfare of Micro, Small, and Medium Entrepreneurs: A Literature Study Review of Economics - Yuliastuti, Ida Ayu Nyoman; Utama, Made Suyana; Marhaeni, Anak Agung Istri Ngurah; Yuliarmi, Ni Nyoman (Journal of The Community Development in Asia, 2024)
Family welfare is the main priority in the nation’s social welfare because the family is the smallest unit in society. The family has an important role in achieving national development goals, so family development is needed to create a prosperous family. The aim of the research is to provide empirical evidence of the influence of human capital, product innovation and online marketing on the welfare of micro, small and medium enterprise entrepreneurs. This scientific article employs qualitative methodologies and conducts literature reviews or library research as its approach. The research results show that human capital plays an important role in maintaining a business in the face of changing market situations. Product innovation carried out in an effort to increase the availability of various products can improve welfare. The use of digital marketing is becoming increasingly important for Micro, Small, dan Medium. Various recommendations can be provided to effectively oversee human capital, innovation, and online marketing in order to enhance human well-being. These include enhancing individuals’ capabilities and skills in adapting and innovating with information technology for business operations, achieved through heightened engagement in relevant training and ongoing studies in the respective field.